(untitled) (Third Sector Social Economic Review, 2021)
In this study, the financial performances of the electricity gas and steam companies, which are quoted in Istanbul Stock Exchange, for the period 2016-2019, were analyzed using the TOPSIS method, one of the multi-purpose decision making methods, and the companies were listed according to the results obtained. While analyzing the firms, the data obtained from the financial statements. In the analysis, liquidity ratios, activity ratios, financial structure ratios and profitability ratios are used from the ratios obtained from the financial statements. According to the data obtained, ""Ayen Enerji Anonim Şirketi"" has shown the best performance in 2016. Between 2017-2019, ""Akenerji Elektrik Üretim Anonim Şirketi"" showed the best performance and ranked at the top. In 2016, ""Enerjisa Enerji Anonim Şirketi"" showed the lowest performance. In 2017, it was observed that ""Zorlu Enerji Elektrik Üretim Anonim Şirketi"" and ""Aksa Energy Üretim Anonim Şirketi"" had the lowest financial performance between 2018-2019.